اتجاهات النخبة الجامعية نحو رقمنة قطاع التعليم العالي - فتح الله بوزيد; كباش الحاج; د-مساعدي حسين (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدراسة باللغة العربية لقد شهد العصر الحالي تقدما تقنيا كبيرا في وسائل وتقنيات الاتصال اللاسلكي والمعلومات الذي استفادت منه العديد من المجالات والقطاعات منها التعليم العالي، الذي يسعى لاستثمار هذا التقدم للوصول إلى تعليم غير حضوري متطور يعتمد أساسا على وسائل وتكنولوجيا الاتصال عالية الكفاءة والجودة، ومما لا شك فيه أن الجامعة كانت ولا تزال من أهم المؤسسات في المجتمع، فهي تمثل نقطة جذب علمي ومصدر إشعاع معرفي تنطلق منه أغلب الأفكار والآراء التي تؤثر في محيطها الاجتماعي. لقد أدى التعلم الإلكتروني، وهو مجموعة متنوعة من تطبيقات التكنولوجيا الإلكترونية في التدريس والتعليم، بالفعل إلى تغييرات كبيرة في التعليم العالي التقليدي القائم على الاقسام الدراسية. وما ذلك، ليس هذا هو تأثيرها الرئيسي ً الوحيد. كما ً يلعب التعلم الإلكتروني أيضا دورا مهما في ظهور عروضا بديلة للتعليم ً العالي. وفي هذه الدراسة سوف نعرض سبب توجهات النخبة نحو الرقمنة في الجامعة الجزائرية وكيف تؤثر على المسار التعليمي والمهني للنخبة. الكلمات الافتتاحية: النخبة الجامعية - الرقمنة- تعليم العالي Summary of the study in English The current era has witnessed great technical progress in the means and techniques of wireless communication and information, which has benefited many fields and sectors, including higher education, which seeks to invest this progress to reach advanced non-attendance education based mainly on highly efficient and high-quality means and technology of communication, and there is no doubt that the university was and still is one of the most important institutions in society, as it represents a scientific attraction and a source of knowledge radiation from which most of the ideas and opinions that affect its social environment are launched. E-learning, a variety of applications of e-technology in teaching and education, has already led to significant changes in traditional higher education, based on classrooms. And so on, this is not the only major impact. E-learning also plays an important role in the emergence of alternative offerings to higher education. In this study, we will present why the elite's attitudes towards digitization at the Algerian university and how they affect the educational and professional path of the elite. Opening Speeches: University Elite - Digitalization - Higher Education.